Herding behavior in cryptocurrency market: evidence from COVID-19, Russia–Ukraine war, and Palestine–Israel conflict - Dhanraj Sharma; Ruchita Verma; Murad Baqis Hasan Al-Bukari; Mohammed A. K. Zaid; Pranav Raghavan (Cogent Economics & Finance)
This study explores herding behavior in the cryptocurrency market during three major international crises: the COVID-19 pandemic, the Russia–Ukraine war, and the Palestine–Israel conflict. The study uses daily closing prices of five major cryptocurrencies (Bitcoin, Ethereum, Tether, BNB, and Solana) and the CRYPTO20 index data from December 31 2019 to May 20, 2024. The research employs the cross-sectional absolute deviation (CSAD) and cross-sectional standard deviation (CSSD) methods to identify herding behavior in the cryptocurrency market. The Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model is used for the robustness check. Stationarity of the data is verified using the Augmented Dickey-Fuller (ADF) test. The empirical findings reveal the anti-herding behavior in the cryptocurrency market during the three sub-periods. The study’s findings have important implications for investors, policymakers, and market regulators. Understanding the dynamics of herding behavior in the cryptocurrency market during global crises can help in developing strategies to mitigate the adverse effects of herding, such as inefficient asset pricing and increased market volatility.